Issues of Criminal Liability for Suicide - Saparovna, Niyozova Salomat; Anvarovich, Otajonov Abrorjon; Khamidov, Nurmukhammad; Sunnatov, Vokhid; Toshev, Otabek (Journal of Ecohumanism, 2025)
This article analyzes the issues of criminal liability for suicide. Also, the article examines issues related to the objective signs of the crime of suicide. The opinions of scientists in this regard were analyzed and relevant suggestions and recommendations were given. In this article, efforts to bring a person to the level of suicide or attempted suicide as a result of intimidation, merciless treatment of a person, or continuous humiliation of his honor and dignity, are analyzed in terms of their objective aspect, and practice materials are studied.